54 EMERGENCY PERIOPERATIVE FOR THE OLDER PERSON SERVICE (POPS) IN AN IRISH TERTIARY HOSPITAL: RESULTS OF 16-WEEK COMPREHENSIVE GERIATRIC ASSESSMENT INTERVENTION. (25th October 2022) - Plant, R; Stanely, E; Dukelow, T; Aherne, E
Abstract: Background: Evidence suggests older persons undergoing surgery benefit from Comprehensive Geriatric Assessment (CGA). The Republic of Ireland (ROI) is yet to implement formalised perioperative care services outside of Orthogeriatrics. We present data from an Emergency Perioperative for Older Person Service (POPS) utilising CGA as an intervention in an Irish Tertiary Hospital. Methods: A geriatric medicine registrar performed CGA on patients over 75 admitted for unscheduled General or Vascular Surgery. Senior decision-makers could refer patients under 75 whom they considered frail. Data collected: demographics; clinical frailty score (CFS); identified delirium; length of stay (LOS); mortality during admission; 90-day mortality; 30-day readmission; new Acute Kidney Injury (AKI) during admission. We compared this data to the corresponding cohort of patients admitted in 2019 (Pre-COVID19 pandemic). Results: 104 patients underwent CGA over 16 weeks. 50.5% (48/104) were female. Average age was 82. 34.6% (36/104) CFS ≥5. 24.2% (23/104) had delirium on admission. 31.7% (33/104) had identifiable delirium throughout their admission. Pre-COVID19 data (n=92) vs POPS data (n=104): Average LOS: 14.6 days vs 13.3 days; AKI new/worse during admission 29% (28/92) vs 15% (16/104); Mortality during admission 8.6% (8/96) vs 7.7% (8/103); 30 day readmission 19.3% (17/88) vs 17.7% (17/96). 90 day mortality 14.1% (13/92) vs 16% (13/80 to date). Conclusion: Our data is, to our knowledge, the first in the ROI to capture CGA intervention in an Emergency Surgical Ward. Early data demonstrate positive trends. We believe the implementation of perioperative CGA would benefit older patients undergoing emergency surgery in Ireland.